Limbaj, Comunicare - Calitatea Vieții - Pânzaru, Petru (Calitatea Vieții, 1993)
The paper presents the theoretical frame for the research done on topic: "Psycho-Social Implication of Social Communications and Language upon Quality of Life during the Transition Period" which consist in defining the essential, even determinating place and role of the psychical and psycho-social factors (generated through communicational activities) in the very deep structure of the socio-human realities. There is also highlighted the incidence which these factors have upon the socio-economical activities’ performance and, through that, upon the quality of life, taking into consideration the specifical conditions from our country, that is situated into a transition period from one type of society and culture to another.